2012
DOI: 10.1039/c2nr30213f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic conductivity of alkyne-capped ruthenium nanoparticles

Abstract: Ruthenium nanoparticles (2.12 ± 0.72 nm in diameter) were stabilized by the self-assembly of alkyne molecules (from 1-hexyne to 1-hexadecyne) onto the Ru surface by virtue of the formation of Ru-vinylidene interfacial linkages. Infrared measurements depicted three vibrational bands at 2050 cm(-1), 1980 cm(-1) and 1950 cm(-1), which were ascribed to the vibrational stretches of the terminal triple bonds that were bound onto the nanoparticle surface. Thermogravimetric analysis showed that there were about 65 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 37 publications
7
36
0
Order By: Relevance
“…As described previously, a significant shift in the C≡C stretch mode was observed on thiol binding to the gold surface indicating the significant electronic coupling between the benzenethiol and the surface. It is noteworthy that the C≡C stretch mode is so sensitive to temperature in this system, as also found in other reports on Raman of alkynes [37]. Their large polarizability renders them sensitive to electronic changes within their molecular vicinity, particularly in conjugated systems [4041].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As described previously, a significant shift in the C≡C stretch mode was observed on thiol binding to the gold surface indicating the significant electronic coupling between the benzenethiol and the surface. It is noteworthy that the C≡C stretch mode is so sensitive to temperature in this system, as also found in other reports on Raman of alkynes [37]. Their large polarizability renders them sensitive to electronic changes within their molecular vicinity, particularly in conjugated systems [4041].…”
Section: Resultssupporting
confidence: 80%
“…The alkyne C≡C stretch mode, which is by far the most intense mode in the powder sample, is reduced in relative intensity in the 2D single-layer array, but remains a dominant feature albeit shifted from 2222 to 2211 cm −1 on surface binding. This suggests a modest weakening of the C≡C bond presumably induced by binding of the thiol to the surface [37]. By comparison, the Raman modes from the S-BPP moiety are weaker than the benzenethiol moiety in the SAM spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The particles exhibited a major absorption peak at around 200 nm ascribing to the p-p* electronic transitions of internal (sp 2 ) graphitic carbons. Figure 1 (b) responses the changes of carbon nanoparticle spectrum to the featureless exponential decay profile anticipating for nanosized Ru particles [15]. This suggested the success of the ruthenium deposition.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, many reports have been generally successfully prepared alkyl vinylidene -linkage to ruthenium core using the special coordinating ligand for example terminal alkyne [1][2][3][4][5] or some vinyl aromatic [6][7]. It is confirmed that alkyne fragments around the metal core do not only functions as protecting ligands promoting the stability of the nanoparticles but also enhances some optical and fluorescence characteristic via the pi-bond interaction between methylene and metal core [8].…”
Section: Introductionmentioning
confidence: 87%
“…It should be noted that similar to ferrocenecarboxylatestabilized ruthenium nanoparticles reported in the previous study, 15 the binding energies of the Ru 3d electrons were somewhat higher than those of alkyne-capped ruthenium nanoparticles because the Ru−O bonds were far more polar than the Ru−C ones. 4 In addition, on the basis of the integrated peak areas, the molar ratio of the COO − carbon to the phenyl ring carbon was estimated to be 1:7.7, close to that (1:10) anticipated from the NAA molecular structure.…”
Section: Methodsmentioning
confidence: 99%